1985
DOI: 10.1246/cl.1985.1835
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Assisted Oxidation of Cyclopentene by Molecular Oxygen

Abstract: Dichlorobis(N,N-dialkylacetamide)palladium(II) complex catalyzes the oxidation of cyclopentene to cyclopentanone by molecular oxygen in alcoholic solvent, in which one atom of molecular oxygen in incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…30 Takehira et al also proposed the formation of Pd(II)-OOH species from palladium, ethanol, and oxygen. 31 Recently, many groups have reported that the Pd(II)-OOH species was believed to be acting as the key intermediate. Thus, H 2 O 2 was produced in the catalytic cycle.…”
Section: Resultsmentioning
confidence: 99%
“…30 Takehira et al also proposed the formation of Pd(II)-OOH species from palladium, ethanol, and oxygen. 31 Recently, many groups have reported that the Pd(II)-OOH species was believed to be acting as the key intermediate. Thus, H 2 O 2 was produced in the catalytic cycle.…”
Section: Resultsmentioning
confidence: 99%
“…46 Finally, because the Pd 0 intermediate in Path B cannot easily account for the formation of olefin isomer cis-2-d-55, we favor syn oxypalladation Path C. The remaining steps of the catalytic cycle involve reprocessing of Pd(II) by molecular oxygen. On the basis of earlier work by Murahashi and Takehira,3g,47 Uemura has proposed that this occurs by insertion of O 2 directly into the [Pd II ]-H to form a Pd-hydroperoxide intermediate. 17a Stahl has elaborated the details of a mechanism for aerobic oxidation catalysis by Pd-(II) that entails reductive elimination of HX from [Pd II ]-H to form Pd(0), which is then oxidized by O 2 in the formation of a Pd-peroxo intermediate.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Takehira and coworkers reported the oxidation of cyclohexene to cyclohexanone with cooxidation of ethanol to acetaldehyde (Figure 4a). 52 Further, a system was developed, which utilizes CuCl 2 in addition to palladium (Figure 4b). 53,54 The authors suggest that a heterobimetallic Pd–Cu(I) species is formed and that the role of copper is as a transient oxygen carrier that facilitates the generation of a Pd–OOH species (Figure 4c).…”
Section: Peroxide-mediated Wacker-type Oxidationsmentioning
confidence: 99%
“…5254 b) The reaction is proposed to occur via alcohol oxidation to provide a Pd–H, into which molecular oxygen can insert. c) The authors suggest an operative Pd–Cu heterobimetallic species.…”
Section: Figurementioning
confidence: 99%